2021
DOI: 10.3390/diagnostics11010128
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Pulmonary Artery Hypertension (PAH) Patients: Observations from a Large PAH Center in New York City

Abstract: Information on outcomes of COVID-19 in pulmonary arterial hypertension (PAH) patients is limited to a few case series and surveys. Here, we describe our experience at a large Pulmonary Hypertension Center in New York City at the height of the pandemic. We performed a retrospective chart review of eleven consecutive PAH patients who were diagnosed with SARS-CoV-2 infection. We analyzed demographics, PAH severity, risk factors for COVID-19, and COVID-19 severity and outcomes. We found in our sample that 63.6% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 18 publications
2
18
0
6
Order By: Relevance
“…If this were the case, VD of the retina measured by OCT-A would be of use as a marker of widespread organ injury in post-COVID-19 patients. Hekimsoy et al 33 have already established a negative correlation between retinal perfusion and idiopathic pulmonary arterial hypertension, a pathology that has been studied in recent times in the context of COVID-19 34 and that results in a higher fatality rate when SARS-CoV-2 infection occurs. Further studies to correlate systemic signs/symptoms are necessary to elucidate this question.…”
Section: Discussionmentioning
confidence: 99%
“…If this were the case, VD of the retina measured by OCT-A would be of use as a marker of widespread organ injury in post-COVID-19 patients. Hekimsoy et al 33 have already established a negative correlation between retinal perfusion and idiopathic pulmonary arterial hypertension, a pathology that has been studied in recent times in the context of COVID-19 34 and that results in a higher fatality rate when SARS-CoV-2 infection occurs. Further studies to correlate systemic signs/symptoms are necessary to elucidate this question.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study from a large pulmonary hypertension centre in New York City, USA, showed that pre-existing chronic pulmonary hypertension has major adverse effects on both the clinical course and mortality associated with COVID-19 (ref. 198 ). By contrast, another study on data from 32 pulmonary hypertension centres in the USA reported a paucity of hospitalized patients with both pulmonary hypertension and COVID-19, and those who developed COVID-19 had mild symptoms and tended to recover quickly 199 .…”
Section: Chronic Sequelae Of Covid-19mentioning
confidence: 99%
“…Pulmonary hypertension is a heterogeneous illness, and only pts with PAH and chronic thromboembolic pulmonary hypertension (CTEPH), i.e., groups 1 and 4 according to WHO classification, are qualified for disease-specific treatment [ 9 ]. It is known that pts with PAH have a high risk of mortality during hospitalizations due to non-cardiovascular diseases [ 10 , 11 , 12 ]. Therefore, the combination of coronavirus infection and pre-existing pulmonary hypertension is a clinically difficult situation associated with a high risk of death, both due to the potentially severe course of COVID-19 and threatened right ventricular failure as a result of the worsening of pulmonary hypertension, e.g., due to hypoxia.…”
Section: Introductionmentioning
confidence: 99%